The ARRE RING-Type E3 Ubiquitin Ligase Negatively Regulates Cuticular Wax Biosynthesis in Arabidopsis thaliana by Controlling ECERIFERUM1 and ECERIFERUM3 Protein Levels - Liu, Shuang; Tong, Meixuezi; Zhao, Lifang; Li, Xin; Kunst, Ljerka (Frontiers in Plant Science, 2021)
The outer epidermal cell walls of plant shoots are covered with a cuticle, a continuous lipid structure that provides protection from desiccation, UV light, pathogens, and insects. The cuticle is mostly composed of cutin and cuticular wax. Cuticular wax synthesis is synchronized with surface area expansion during plant development and is associated with plant responses to biotic and abiotic stresses. Cuticular wax deposition is tightly regulated by well-established transcriptional and post-transcriptional regulatory mechanisms, as well as post-translationally via the ubiquitin-26S proteasome system (UPS). The UPS is highly conserved in eukaryotes and involves the covalent attachment of polyubiquitin chains to the target protein by an E3 ligase, followed by the degradation of the modified protein by the 26S proteasome. A large number of E3 ligases are encoded in the Arabidopsis genome, but only a few have been implicated in the regulation of cuticular wax deposition. In this study, we have conducted an E3 ligase reverse genetic screen and identified a novel RING-type E3 ubiquitin ligase, AtARRE, which negatively regulates wax biosynthesis in Arabidopsis. Plants overexpressing AtARRE exhibit glossy stems and siliques, reduced fertility and fusion between aerial organs. Wax load and wax compositional analyses of AtARRE overexpressors showed that the alkane-forming branch of the wax biosynthetic pathway is affected. Co-expression of AtARRE and candidate target proteins involved in alkane formation in both N. benthamiana and stable Arabidopsis transgenic lines demonstrated that AtARRE promotes the turnover of wax biosynthetic enzymes ECERIFERUM1 (CER1) and ECERIFERUM3 (CER3). CER1 has also been confirmed to be a ubiquitination substrate of the AtARRE E3 ligase by an in vivo ubiquitination assay using a reconstituted E. coli system. The AtARRE gene is expressed throughout the plant, with the highest expression detected in fully expanded rosette leaves and oldest stem internodes. AtARRE gene expression can also be induced by exposure to pathogens. These findings reveal that wax biosynthesis in mature plant tissues and in response to pathogen infection is controlled post-translationally.